1998
DOI: 10.1046/j.1365-2893.1998.00112.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection and related chronic liver disease in a resident elderly population: the Silea study

Abstract: The prevalence of hepatitis C virus (HCV) infection increases with advancing age, but the disease has been poorly studied in the elderly. A population-based study was therefore carried out to investigate the prevalence of HCV infection and the severity of HCV-related chronic liver disease in the elderly. One thousand and sixty-three people (> or = 60 years of age) were screened for antibodies to HCV (anti-HCV) and for possible abnormalities of common liver function tests. Positive subjects and sex and age-matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Using a first-generation enzyme-linked immunosorbent assay, we found a surprisingly low prevalence of anti-HCV in institutionalized aged subjects [5]. More recently, comparable findings have been reported in a seroepidemiological study carried out in a nursing home in northeast Italy [6].…”
Section: Introductionsupporting
confidence: 84%
“…Using a first-generation enzyme-linked immunosorbent assay, we found a surprisingly low prevalence of anti-HCV in institutionalized aged subjects [5]. More recently, comparable findings have been reported in a seroepidemiological study carried out in a nursing home in northeast Italy [6].…”
Section: Introductionsupporting
confidence: 84%
“…In another Italian study, the prevalence of positive HCV antibody was reported to be 3.3% among 1063 people aged 60 years or older (5). From those who were positive for HCV antibody, 19 subjects (54.3%) had detectable HCV RNA (5).…”
Section: Epidemiologymentioning
confidence: 99%
“…From those who were positive for HCV antibody, 19 subjects (54.3%) had detectable HCV RNA (5). HCV genotype 2a was the most common genotype among those who had positive HCV RNA with a prevalence of 68.4% (5).…”
Section: Epidemiologymentioning
confidence: 99%
“…Prevalence of chronic HCV infection among patients aged 60 years in Italy and Japan reportedly ranges between 3.3 and 13.1% [19,20], and these patients often have advanced liver disease [6]. Patients aged C65 years were excluded from therapeutic trials evaluating the safety and efficacy of the current standard-of-care for the treatment of HCV-PEG-IFN and ribavirin-and in clinical practice, elderly patients are also often deemed not eligible for antiviral therapy [8,9].…”
Section: Discussionmentioning
confidence: 99%